3-(4-Chloroanilino)-5,5-dimethylcyclohex-2-en-1-one - Sumati Anthal (Acta Crystallographica Section E, 2012)
The asymmetric unit of the title compound, C14H16ClNO, contains two independent molecules, both with the cyclohexene ring in a sofa conformation. In the crystal, N—H...O hydrogen bonds link the molecules related by translation along the a axis into two crystallographically independent chains. Weak C—H...π interactions are also observed.